Pencegahan Perilaku Negatif Peserta Didik Melalui Metode Bercerita - Hayati, Eti; Siswandi, R. Dede; Hardi, Ruli (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2025)
Bullying behavior can cause psychological trauma or emotional wounds, both for victims and perpetrators. Therefore, it is important to pay attention to mental health for students, especially to have the courage to tell everything they experience, both to their teachers and their parents in teaching children about the dangers of bullying behavior so that they do not become perpetrators or victims. This is where the role of parents, teachers and schools to play an active role in socializing for prevention, especially in the learning process in the classroom. Many ways to prevent bullying behavior can be done, including through good and open communication. Ask how children feel during school to tell, build children's self-confidence. When they know their abilities and feelings about themselves, feelings of intimidation they may feel will decrease. Then instill an anti-bullying mindset by not teaching shouting, hitting, pushing and teasing others and teach students how to deal with bullying. Then provide motivation and courage to report to teachers or parents if they experience or see bullying behavior among their friends. In addition to the role of parents in preventing bullying, teachers also play a significant role, as they can incorporate this into the learning process. The role of teachers in preventing bullying is crucial, as they are at the forefront of creating a safe and supportive environment for students.